PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN PELANCONG KE M-BLOC SPACE JAKARTA PADA ERA NEW NORMAL - Audrey, Natasha; Sudiarta, I Nyoman; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
Promotion mix is one way that can be done by the company to market a product or service. With promotion mix, consumers can find out information about a product or a tourist destination. One of the tourist destinations that carry out promotional mix activities is the M-Bloc Space Jakarta area. The purpose of this study was to determine the effect of promotional scatter on the decision to visit M-Bloc Space Jakarta in the New Normal Era. The operational definition of the variables used in this study is the Promotional Mix which consists of four sub-variables advertising (X1), sales promotion (X2), public relations (X3) direct marketing (X4) and visiting decision variables (Y). Data was collected using observation, literature study, documentation and distributing questionnaires with the help of google form to 85 respondents with purposive sampling. The data analysis technique in this study used multiple linear regression analysis. Based on the results of the research, it is known that the promotion mix variables which consist of advertising (X1), public relations (X3) and direct marketing (X4) affect the decision to visit M-Bloc Space Jakarta. While the sales promotion variable (X2) has no effect on the decision to visit M-Bloc Space Jakarta. Furthermore, based on the results of the F test, it shows that the promotion mix variable simultaneously influences the decision to visit M-Bloc Space Jakarta in the New Normal Era with a coefficient of determination value of 63% and the rest is influenced by other factors.